Compositional variation in columbite-group minerals from different types of granitic pegmatites of the Erajarvi district, South Finland - Lahti,S.I. (Journal of the Czech Geological Society, 2000)
Compositional variation of columbite-group minerals in different LCT-types of granitic pegmatites of the Erajarvi district, Orivesi, South Finland, was studied by 611 electron-microprobe analyses of 145 crystals that were collected from 30 beryl-columbite pegmatites, 15 beryl-columbite-phosphate pegmatites and one complex pegmatite of the amblygonite subtype. Fe, Mn, Nb and Ta dominate the composition, but the minerals may include some Ti (< 0.1 apfu) and Sn, W, and Sc (< 0.05 apfu each) as well. Progressive enrichment of Mn and Ta in columbite-group minerals from the most primitive beryl-columbite pegmatites to the highly fractioned complex pegmatites is a significant overall feature in the pegmatite sequence, although the increase in both Mn/(Mn+Fe) and Ta/(Ta+Nb) in the mineral is not proportional in the different types of the dykes. The average values of Mn/(Mn+Fe) and Ta/(Ta+Nb) in the columbite-group minerals increase markedly from beryl-columbite pegmatites (0.39 and 0.24, respectively) to beryl-columbite-phosphate pegmatites (0.47 and 0.48, respectively), and the values are highest in the Viitaniemi amblygonite pegmatite (0.79 and 0.51, respectively). In the beryl-columbite pegmatites, the variation in Mn/(Mn+Fe) of columbite-group minerals is extensive, but that of Ta/(Ta+Nb) limited. Ferrocolumbite is most common and manganocolumbite is encountered in the more evolved dykes of this category. In the beryl-columbite-phosphate pegmatites, which also contain triphylite-lithiophilite as a characteristic accessory mineral, Ta/(Ta+Nb) increases much more than Mn/(Mn+Fe) during pegmatite evolution. Ferrocolumbite occurs in the marginal, ferrotantalite and minor manganocolumbite in the central parts of the dykes. Concomitant increase in Mn/(Mn+Fe) and Ta/(Ta+Nb) with pegmatite evolution is characteristic of columbite-group minerals from the complex pegmatites enriched in Li minerals such as elbaite, lepidolite, spodumene and amblygonite-montebrasite. Manganocolumbite and manganotantalite are characteristic of this type of dykes, but their marginal zones may also contain minor ferrocolumbite. The compositional trend of columbite-group minerals from the Viitaniemi pegmatite, a typical complex pegmatite of the amblygonite subtype, extends from the ferrocolumbite field through the manganocolumbite field up toward the manganotantalite corner of the columbite quadrilateral.
Keywords: Ferrocolumbite; ferrotantalite; manganocolumbite; manganotantalite; chemical composition; granitic pegmatite; granite; Proterozoic; Erajarvi; Orivesi; Finland